Faktor Penurunan Minat Masyarakat Dalam Menonton Televisi: Studi pada Masyarakat Desa Bayu Kecamatan Darul Imarah Kabupaten Aceh besar - Wilda Sofia; Ade Irma (Sadida Islamic Communications and Media Studies, 2025)
In the era of technological development, mass media continues to give birth to changes for new media that can rival television. The results of a Nielsen survey in 2019 show that there was a decline in television viewership of around 2-5%. Factors that affect viewing interest according to De Fluer are broadcast duration, broadcast frequency, and broadcast program. The purpose of this study is to see how much the factors of broadcast duration, broadcast programs, and broadcast frequencies affect people's interest in watching. This study uses a qualitative approach with descriptive analysis techniques. The data collection method in this study was carried out by means of interviews, observations, and documentation. The results of this study show that the indicators used (broadcast duration, broadcast frequency, broadcast program) have an effect on the decrease in interest in watching television in the people of Gampong Bayu, Darul Imarah District. The frequency has an effect because the broadcast schedule of television broadcasts does not match the time of the audience. Then the duration of the broadcast tends to be too short compared to com commercial breaks, so that people's interest in watching decreases. Broadcast programs that are less educational and less informative make people less interested in watching television.